Pengaruh Pemahaman, Sanksi Perpajakan, dan Tingkat kepercayaan pada Pemerintah terhadap Kepatuhan Wajib Pajak dalam Membayar PBB-P2 - Rahmat Yuliansyah; Desy Amaliati Setiawan; Rayahu Sri Mumpuni (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2019)
- This research aims to knowing effect understanding tax, tax sanction, and level of trust in the goverment againts taxpayers compliance in paying land and building tax - rural and urban in the sub-district Jatinegara. The population in this research were PBB-P2 taxpayers registered in Jatinegara sub-district as many as 27,761 taxpayers. The sample in this study amounted to 100 taxpayers obtained from the results of calculations using the Slovin formula. The method of collecting data in this study by distributing questionnaires. Questionnaire tests in this research, namely data quality test, classic assumption test, and hypothesis test. The results of this research indicate that there is a significant effect of the understanding variable on taxpayer compliance in PBB-P2 payments. This is evidenced by the positive regression coefficient (0.307) and tcount greater than the value of ttable (4.408> 1.98498) at the significance value (0,000 < 5%). There is a significant effect of tax sanction variable on taxpayer compliance in PBB-P2 payments. This is evidenced by the negative regression coefficient (-0.209) and tcount smaller than the value of ttable (-1.452 < 1.98498) at the significance value (0,150 > 5%). There is a significant effect of the level of trust in the government variable on taxpayer compliance in PBB-P2 payments. This is evidenced by the positive regression coefficient (0.654) and tcount greater than the value of ttable (6.540 > 1.98498) at the significance value (0,000 < 5%). Understanding, tax Sanctions, and the level of trust in the government have a significant effect of a manner together on taxpayers compliance in PBB-P2 payments. This is evidenced by the value of Fcount which is greater than the value of Ftable (28,113 > 2,70) at the significance value (0,000 < 5%).